Peritoneal dialysis catheter dysfunction due to fibrin clots following treatment with tranexamic acid: a clinical case - Elodie Bogner; Elodie Ferrero; Joelle Marin; Stanislas Bataille (RDPLF, 2021)
Chronic kidney disease patients experience not only more frequent arterial and venous thrombosis but also hemorrhagic episodes. Tranexamic acid is an anti-fibrinolytic molecule that inhibits plasmin activation. It is used in hemorrhage cases (post-traumatic, gynecologic, or gastrointestinal bleeding). We report on an original case of tranexamic acid (Exacyl®) use in a peritoneal dialysis patient for gastrointestinal bleeding of unknown origin. The use of tranexamic acid led to the Tenckhoff catheter dysfunction because of fibrin clots in the dialysate. The emergence of fibrin clots a few days after the start of tranexamic acid treatment, which never occurred again after the end of the treatment, and the anti-fibrinolytic function of tranexamic acid favors this treatment's role in fibrin clot occurrence.